Technostress in times of change: unveiling the impact of leadership styles in Cambodia's public organizations in the wake of COVID-19 - Bora Ly; Romny Ly (Cogent Business & Management, 2024)
This study examines the impact of different leadership styles on technostress within public organizations in Cambodia amidst the challenges of the COVID-19 pandemic. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 351 employees working in various public organizations across Cambodia. The study specifically investigates the relationships between three leadership styles—transformational, transactional, and laissez-faire—and the level of technostress experienced by employees. The findings reveal a statistically significant and positive relationship between transformational leadership and a reduction in technostress, suggesting that transformational leadership qualities such as inspiration, motivation, and individualized consideration effectively mitigate the adverse effects of technostress. Conversely, transactional and laissez-faire leadership styles are positively associated with increased levels of technostress, indicating that these styles may exacerbate the stress employees experience in response to technological changes and challenges. The study contributes to the existing literature by providing empirical evidence on the impact of leadership styles on technostress in a unique cultural and organizational context. It offers valuable insights for policymakers, organizational leaders, and practitioners in understanding the role of leadership in managing technostress, especially during times of crisis and rapid technological change. The study also highlights the importance of leadership development programs in public sector organizations that emphasize leadership styles that help reduce technostress. The findings emphasize the need for a balanced approach to leadership that considers both the demands of technological adaptation and the well-being of employees.This research offers key insights into how leadership styles in Cambodian public organizations impact employees' stress levels due to technology, particularly during the Covid-19 pandemic. It reveals that leaders who inspire and support their teams (transformational leaders) can significantly reduce technology-related stress. In contrast, more directive or hands-off leadership approaches (transactional and laissez-faire) tend to increase such stress. This study is particularly relevant in our current era of rapid technological change, highlighting the crucial role of leadership in managing the challenges of technology in the workplace. For the general public, it underscores the importance of empathetic and supportive leadership in reducing workplace stress in a tech-driven world.
Keywords: 650; Technostress; leadership styles; transformational leadership; transactional leadership; laissez-faire leadership; PLS-SEM; Covid-19; public sector; Cambodia